2020
DOI: 10.1016/j.molcel.2019.11.016
|View full text |Cite
|
Sign up to set email alerts
|

The Chaperone FACT and Histone H2B Ubiquitination Maintain S. pombe Genome Architecture through Genic and Subtelomeric Functions

Abstract: The chaperone FACT and histone H2B ubiquitination maintain S. pombe genome architecture through genic and subtelomeric functions

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
44
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(55 citation statements)
references
References 67 publications
(76 reference statements)
7
44
1
3
Order By: Relevance
“…While this work was under review, Murawska et al reported a role for H2Bub1 in suppressing antisense transcription in S. pombe , consistent with the findings reported here ( 54 ). Their study indicated that loss of H2Bub1 increased antisense transcription by allowing an aberrant activity of the FACT histone chaperone complex.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…While this work was under review, Murawska et al reported a role for H2Bub1 in suppressing antisense transcription in S. pombe , consistent with the findings reported here ( 54 ). Their study indicated that loss of H2Bub1 increased antisense transcription by allowing an aberrant activity of the FACT histone chaperone complex.…”
Section: Discussionsupporting
confidence: 90%
“…At the CPS, reduction in the pSpt5/Spt5 ratio occurs 5′ of a similar reduction in H2Bub1/H2B ratio; the latter effect is a result of nucleosome removal. Loss of H2Bub1 through histone turnover near the CPS was observed in another recent study ( 54 ). This suggests that Spt5 dephosphorylation might trigger chromatin remodeling events leading to H2Bub1 removal at the 3′ ends of genes.…”
Section: Discussionsupporting
confidence: 60%
“…Despite the low levels of H3K36 methylation, interestingly, knob formation requires Set2, a sole methyltransferase of H3K36 in S. pombe. It has also been shown that the kinetochore protein Sgo2, FACT (facilitates chromatin transcription), which is an essential histone chaperon consisting of Spt16 and Pob3, and the mono ubiquitinated histone H2B (H2Bub) are required for knob formation [102,103]. H2Bub facilitates histone H2A/H2B dimer deposition by FACT.…”
Section: Dapi-dense "Knob" Regionmentioning
confidence: 99%
“…H2Bub facilitates histone H2A/H2B dimer deposition by FACT. In addition, FACT maintains the nucleosome density in the sub-telomeric region [103], which may be the key to knob formation. The border between the heterochromatin and euchromatin is also controlled by the anti-silencing factor, Epe1 [90,91].…”
Section: Dapi-dense "Knob" Regionmentioning
confidence: 99%
See 1 more Smart Citation